Modernization of methods of work with gifted children as a constituent part of the process of implementing the New Ukrainian School Concept - Karpova, L (Problems of Engineer-Pedagogical Education, 2019)
The article traces the way the views on giftedness have developed throughout the history, defines the essence of the concept of teaching methods and analyzes the necessary competencies of the teacher applicable while working with gifted children. The paper provides examples of some successful in the developed countries approaches to the development and contents of educational trajectories designed to work with gifted children. The article considers components of the Law of Ukraine "On Education", which provide for the autonomy of schools and new forms of getting education, grant pedagogical freedom to teachers by giving them the authority to compose educational and training programs based on the needs of a particular class, students’ abilities and their interests, and provide for the differentiation of teachers’ wage rates through voluntary certification. The author recommends differentiating the educational process for gifted children in general schools in the context of implementing the New Ukrainian School Concept through the individualization of education. The article contains a list of innovative teaching methods to work with gifted school students. In order to modernize individual education options for capable students and to improve the professional level of teachers, the author suggests that teachers take refresher courses with regard to this specificity.